Shattered dreams : a Midnight dragonfly novel - James, Ellie (St. Martin's Griffin, 2011)
After her grandmother's death, sixteen-year-old orphan Trinity Monsour moves to New Orleans to live with her aunt, hoping to lead a normal life, but her frightening visions not only prevent her from feeling normal, they make her a suspect in the disappearance of a classmate.